A resource-constrained profit-based dynamic order management model. (21st February 2008) - Kirche, Elias T.; Srivastava, Rajesh
This research extends the Available-to-Promise (ATP) concept to include both capacity and profitability considerations in a two-level supply chain. The model in study is referred in practice as Profitable-to-Promise (PTP) logic. It provides a decision support system for companies to determine order profitability in real time environment, and allows for order promising and critical resource planning. The efficiency of the PTP model is investigated by comparing it with a capacity decision rule with customer specified due date. Results suggest that capacity loadings influence the choice of model, with the PTP model preferred at higher capacity loadings.